2004
DOI: 10.1002/ijc.20655
|View full text |Cite
|
Sign up to set email alerts
|

Persistence of bone marrow micrometastases in patients receiving adjuvant therapy for breast cancer: Results at 4 years

Abstract: We have previously developed a quantitative PCR (QPCR) technique for the detection of cytokeratin 19 (CK19) transcripts in blood and bone marrow and compared this to immunocytochemistry (ICC).Together, both have shown promise for monitoring therapeutic efficacy in patients with metastatic breast cancer. The aim of this study was to determine the feasibility and value of these assays for minimal residual disease (MRD) in monitoring efficacy of adjuvant therapy following surgery for primary breast cancer. Bone m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
58
1
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 65 publications
(62 citation statements)
references
References 49 publications
2
58
1
1
Order By: Relevance
“…We have previously published the fact that there is occasional evidence of DTCs on follow-up of patients over 4 years after treatment for primary breast cancer (Slade et al, 2005). Most patients show considerable variability.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We have previously published the fact that there is occasional evidence of DTCs on follow-up of patients over 4 years after treatment for primary breast cancer (Slade et al, 2005). Most patients show considerable variability.…”
Section: Discussionmentioning
confidence: 99%
“…To have a group of patients who were at very low risk of having recurrence in the future, we decided to take the subset of patients from our published study (Slade et al, 2005) to include only those patients with T 1 N 0 (i.e., those who had a tumour p2 cm)and who were node negative (group II) 4 -13 years post-surgery. For the high-risk group (group III), we included patients who previously had 43 node-positive breast cancer (with one exception, a patient with two positive nodes) and were on follow-up and who had no sign or symptom of recurrence.…”
Section: Breast Cancer Patientsmentioning
confidence: 99%
See 1 more Smart Citation
“…All samples were normalized for ABL gene expression, which has been reported in several breast cancer papers as reference gene to normalize RT-PCR data. [20][21][22][23] The ABL forward primer was 5 0 -CGTCCTCCAGCTGTTATCTGG-3 0 and reverse primer was 5 0 -CACTCAGACCCTGAGGCTCAA-3 0 . All primers were designed with Primer Express Software.…”
Section: Tissue Processing and Real-time Quantitative Rt-pcrmentioning
confidence: 99%
“…Where long-term survival has been examined, it has mostly been shown that women with breast cancer continue to experience excess mortality into the second and third decades after their diagnosis (Duncan and Kerr, 1976;Langlands et al, 1979;Brinkley and Haybittle, 1984;Adami et al, 1986;Zahl and Tretli, 1997;Joensuu et al, 1999). This excess mortality may be due to the existence of 'micro-metastases' -disseminated cancer cells present even in women with apparently localised disease at diagnosis (Slade et al, 2005). Because previous survival studies have been based on cohort or complete approaches, trends in longterm survival have involved women diagnosed from the 1940s up to the 1970s, at least 10 years before the important advances in diagnosis and management that occurred during the 1980s.…”
mentioning
confidence: 99%